Conformationally flexible arylethynyl bis-urea receptors bind disparate oxoanions with similar, high affinities. Issue 94 (9th October 2018) - Eytel, Lisa M.; Brueckner, Alexander C.; Lohrman, Jessica A.; Haley, Michael M.; Cheong, Paul H.-Y.; Johnson, Darren W.
Abstract : Despite competing trends and computational predictions to the contrary, three bis-urea receptors bind disparate oxoanions (ClO4 −, HSO4 −, H2 PO4 − ) with equal affinities in a non-polar solvent; in a more polar solvent the trend in association constants for one receptor matches that of the p K b of the guest, as expected for H-bond donating hosts. Abstract : Conformationally flexible hosts with relatively small binding pockets are seldom shown to bind oxoanions preferentially over other guests. Herein, we disclose the binding of diprotic, monoprotic, and aprotic tetrahedral oxoanions with three different pyridylethynyl bis-urea scaffolds. In less polar solvent, the trend in association constants appears to be heavily influenced by solvation and entropic effects. However, in a more polar solvent, the trend in association constants matches that of the p K a of the conjugate acid of the anionic guest, as expected for H-bond donating hosts.